The genome of business excellence and business culture of the production organization – the basis of the culture of production relations of society - Savenko, V.I.; Nesterenko, I.S.; Shatrova, I.A.; Demidova, Е.А.; Orlyk, Y. (Ways to Improve Construction Efficiency, 2021)
The genome of business excellence and business culture of the production organization – the basis of the culture of production relations of society